Socio-economic degeneration of rural Maguindanaons: contributions of colonialism and political instability - Abdul, Pute Makol (1988)
The long and complex history of interactions between the Muslims and the Spanish and American colonialists in the Philippines have resulted in marked changes in the political, economic and social life of the Maguindanaon Muslims which have persisted to the present time. The situation of the tribe became worsened when they were forcibly incorporated into the Philippine State controlled by politically and socioculturally culminated in the Mindanao civil war in phenomenon of violence has also helped structure of Maguindanaon society.